Visual inspection with Acetic Acid (VIA) as an Alternative to Colposcopy in Detection of Cervical Carcinoma in low recourses setting - Deepa Masand; Smarika Dubey (International Journal of Medical Research and Review, 2014)
Objective: To evaluate visual inspection with acetic acid ( VIA ) as an alternative to colposcopy in detection of cervical carcinoma in low resource setting.Introduction: Cervical cancer is a major public health problem in developing countries, with India itself accounting for one-fifth of the global burden of the disease. In low resource settings, screening of CIN and carcinoma cervix by colposcopy can be replaced by cheaper and easily available visual methods like VIA, which has the high sensitivity to detect any grade of dysplasia.Method: VIA was performed in two hundred symptomatic women as a pre colposcopy attending the gynaecology department at National Institute of Medical Science ( NIMS ) Hospital Jaipur. Sensitivity of VIA was calculated.Result: Out of 200 patients VIA was positive in 48 (24%) cases. In VIA positive cases, Colposcopy was abnormal in 30 ( 62.5%). In VIA negative cases colposcopy was abnormal in only in 2 (1.3%) cases. 32 cases with abnormal colposcopic finding were subjected to biopsy.Conclusion: The high Sensitivity of 86.6% of VIA shows that most of the preinvasive and invasive lesion were picked up by VIA. Thus VIA could be valuable in detection of precancerous lesion of the cervix in low resource setting.